Suitable growth conditions and nutrition factors on in vitro culture of Phlebopus portentosus (Boletales) - Kumla J. (2014)
Phlebopus portentosus is one of the most popular wild edible mushrooms in northern Thailand. As this mushroom may not be obligately ectomycorrhizal, we look into the possibilities for its commercial cultivation. In this paper we report the effects of pH, temperature, carbon and nitrogen sources and 15 culture growth media on the growth of P. portentosus. The results indicated that mycelia of P. portentosus grow well at pH 4.0. The fungus was able to grow at temperatures ranging from 20-35°C, with an optimal growth temperature of 30°C. Glucose and ammonium salts produced the largest radial growth. Among 15 culture media tested, modified Murashige & Skoog and fungal-host media were the best for the mycelia growth. Sclerotia-like structures were formed on these media after three weeks of incubation.